Study of ZnO Nanorods Based Perovskite Solar Cells At Varying Pressure - Ajay Pratap Singh Gahlot, Ayushi Paliwal, Avinashi Kapoor (International Journal of Advanced Science and Technology, 2020)
Perovskite solar cells have drawn remarkable attention for the past few years. In order to enhance the efficiency of solar cells, electron transporting layer (ETL) is used. Due to high transparency and electron mobility, Zinc Oxide (ZnO) is the appropriate material as an electron transporting layer. In the present work, an effort has been made to synthesize the ZnO nanorods using Pulsed laser deposition (PLD) technique by varying its deposition pressure. Integrating it with MAPbI3 so as to study its light harvesting efficiency for perovskite solar cell application.